Assessment of silver-stained AFLP markers for studying DNA polymorphism in proso millet (Panicum miliaceum L.) - Karam,Décio (2006)
Proso millet (Panicum miliaceum L.) is a serious weed in North America. A high number of wild proso millet biotypes are known but the genetic basis of its phenotypic variation is poorly understood. In the present study, a non-radioactive silver staining method for PCR-Amplified Fragment Length Polymorphism (AFLP) was evaluated for studying genetic polymorphism in American proso millet biotypes. Twelve biotypes and eight primer combinations with two/three and three/three selective nucleotides were used. Pair of primers with two/three selective nucleotides produced the highest number of amplified DNA fragments, while pair of primers with three/three selective nucleotides were more effective for revealing more polymorphic DNA fragments. The two better primer combinations were EcoR-AAC/Mse-CTT and EcoR-ACT/Mse-CAA with seven and eleven polymorphic DNA fragments, respectively. In a total of 450 amplified fragments, at least 339 appeared well separated in a silver stained acrylamide gel and 39 polymorphic DNA bands were scored. The level of polymorphic DNA (11.5%) using only eight pairs of primers were effective for grouping proso millet biotypes in two clusters but insufficient for separating hybrid biotypes from wild and crop. Nevertheless, the present result indicates that silver stained AFLP markers could be a cheap and important tool for studying genetic relationships in proso millet.